Economic Development and Capacity Building for Rural Communities through Oyster Mushroom Cultivation - Wajdi, Muh Barid Nizarudin; Saini, Mukhamat; Sabana, Moh. Bahrulloh; Fu'in, Hilwa Saida; Nashihah, Risalatun (STAI Miftahul ULa Nganjuk, 2024)
This study explores the potential of oyster mushroom cultivation as a tool for economic empowerment in Garu Village, utilizing the Asset-Based Community Development (ABCD) framework. The research examines the implementation of a community-based intervention aimed at increasing local economic opportunities through sustainable mushroom farming. Data were collected through participant observations and interviews with local vendors, assessing the impact of the intervention on income generation, market reach, and community involvement. The results indicate that the program significantly improved the participants' ability to cultivate and market oyster mushrooms, leading to increased sales and enhanced community participation in agricultural activities. Despite the success of the initiative, challenges such as marketing strategies and production quality remain, highlighting areas for improvement. The study concludes that oyster mushroom cultivation, combined with community-driven empowerment, can foster sustainable economic growth in rural communities, offering valuable insights for similar interventions in other regions.